Pengembangan Komik Digital Interaktif Berbasis Canva untuk Peningkatan Hasil Belajar Siswa Sekolah Dasar - Safitri, Yuliana; Widodo, Susilo Tri (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – Student learning outcomes are still low in the material of Indonesian Cultural Diversity. Therefore, interactive learning media is needed, namely digital comics. The purpose of this research is to develop learning media in the form of digital comics and test their feasibility and effectiveness to improve learning outcomes.Method – This research used a development approach (Research and Development), based on the Borg & Gall model. Data collection techniques used test techniques (one group pretest-post test) and non-test techniques (observation, interviews, documentation, and questionnaires). Findings – Digital comics were developed into interactive media with hyperlink innovation. This media is very feasible and obtained a percentage of 95.31% from material experts and media expert validators. Positive responses from teachers and students obtained a percentage of 90.38% and 80.95%. The effectiveness of the media was carried out with one group pretest posttest with an N-Gain value of 0.6663 which means moderate with a percentage of 66% quite effective. Canva-based digital comic media is very feasible to be tested and can improve student learning outcomes about Indonesian Cultural Diversity material. Research Implications – These findings reinforce the constructivist approach, which emphasizes that students actively construct knowledge through meaningful learning experiences. The use of hyperlinked digital comics creates a context-rich learning environment aligned with the principles of multimedia learning and problem-based learning, suggesting their potential as effective tools to enhance engagement and critical thinking in educational settings.